Influence of price and product information on purchase intention for home personal computers (PCs) in Malaysia - Low, Kay Wui (1999)
Price and product information are empirically examined to see their influence on purchase intention. These are done together with three intervening variables namely perceived price, perceived quality and perceived value. The aim of this study is to find out how customers use product attribute and price information in the evaluations of a product. A survey was conducted amongst students to find out whether price and product information has any influence on their purchase of a home PC. Two levels of price were included in the questionnaire. The price levels are specified to create large differences in price as to facilitate measuring its impact on consumers' perceptions of quality but at the same time to be considered realistic by respondents. The high prices were selected to be close to the upper ends of the price ranges in local markets, and the low prices close to the lower ends. Linear regression analysis was used to examine the hypotheses. This study indicates that consumers' price perception is positively influenced by objective price and negatively influenced by reference price, which implies that before deciding on appropriate price levels for target customers, marketers should know consumers' internal standards. The findings also indicates that perceived quality and perceived price act directly on purchase intention. At the same time, it is found that the purchase intention is influenced by perceived value. A future research could be done in this area and more variables could be brought into the model.